Effect of Calcination on The Bioactivity of Hydroxyapatite (HAp) from Black Tilapia Fish Scale - Noor Hakim Rafai; Muhamad Zaki Jaffri; Hasan Zuhudi Abdullah; Maizlinda Izwana Idris (International Journal of Integrated Engineering, 2025)
Hydroxyapatite, HAp is extensively used for orthopaedic and dental reconstruction as implant material due to their chemical and biological similarity to human hard tissue. Recently, vigorous research efforts made to obtain HAp from an animal bone in providing alternative feedstock materials for biomedical applications. Therefore, the extraction of natural HAp from the Black Tilapia (Oreochromis Niloticus) fish scales was produced via a conventional heat treatment (calcination) at 1000 °C. To produce HAp fine powder, the natural HAp from the tilapia fish scale went through a grinding process before characterization and testing. The sample was characterized using powder X- rays Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Energy Dispersive X-ray spectroscopy (EDX). The bioactivity of the samples was characterized using a Simulated Body Fluid (SBF) Test, Anti-Microbial and MTT-assay using a Human Fetal Osteoblast (hFOB) 1.19 cell line. XRD result shows the crystallinity of extracted HAp is similar to the standard HAp. The FESEM image shows the particles have different morphologies. The EDX analysis shows that the Ca/P ratio is 1.69 that slightly different from the standard HAp (1.67). The SBF result shows apatite deposition on top of the pellet sample surface after immersion for 7 days. Anti-Microbial shows that there are no anti-microbial properties on the extracted HAp and the MTT-assay analysis shows that the samples were not toxic to the cell. This work shows that studies on the extraction of fish scale into high value-added product are the promising alternative to produce natural HAp that is beneficial to medical applications. The bioactivities show that the natural HAp produced is bioactive and not toxic.